Pemanfaatan Media Interaktif Dalam Pembelajaran Bahasa Arab: Sebuah Studi Literatur - Romadhon, Moh. Sahru; Winaryo, Nugroho; Rohib, Agus; Ahsanuddin, Mohammad (Prosiding Konferensi Nasional Bahasa Arab, 2023)
Arabic language learning is a complex process that requires the role of effective learning media. This article explores a wide range of interactive media that can be used in the Arabic language learning process, including hypertext, hypermedia, multimedia resources, web-based resources, and intelligent television. The research method is desk research which involves analyzing various sources and related documents. The results show that the use of interactive media in Arabic language learning can increase student motivation and learning effectiveness. Some of the interactive media discussed include interactive CDs, learning applications such as Kahoot, Duolingo, and, as well as the use of the internet through Arabic websites. Although they have various advantages such as innovation in learning and increased student motivation, some disadvantages such as program complexity and lack of information structure also need to be considered. Thus, this article provides valuable insights into the importance of utilizing interactive media in the Arabic language learning process.